IMPACT OF SKILLS DEVELOPMENT PROGRAMME IN HANDICRAFT ARTISANS OF MANIPUR - Phuritsabam, Bobby; Larellapam, Seilendra; Mayanglambam, Prabin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Handicraft is a labour-intensive sub-sector with high potential of employment for poor section of society in rural areas. It is economically important because of the low capital investment, high value addition and negotiable import content and high potential for export earnings. Skills development and knowledge are the driving forces of economic growth as well as social development for a nation. Traditionally, the artisans have been backbone of the Economy of the Indian rural society. It is fact that young people are the innovators, creators, leaders, and builders of the future. But they can transform the future only if they have innovative skills, health standard, decision-making, financial aid as well as real choices in life. Over the past few years, we have repeatedly placed excessive faith in India's demographic dividend. Some even take it too far, and predict how this will lead us to economic super dome. Current study mainly, focusing on skill development among handicraft artisans and its impact on employment generation especially in Manipur State. It throws the light on impact of government training centres on artisans, income of skilled artisans and unskilled artisans and younger generations concerns whether they are inclined towards handicraft sector or not. The sample artisans are taken from the two districts of Manipur.